Red cell distribution width and mean platelet volume in patients with irritable bowel syndrome - Aktas, Gulali; Alcelik, Aytekin; Tekce, Buket Kin; Tekelioglu, Vildan; Sit, Mustafa; Savli, Haluk (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction: Possible pathophysiological mechanisms of irritable bowel syndrome (IBS) are interactions between microbial flora of the gut and the mucosal/systemic immune system, post-infectious status and inflammation. Mean platelet volume (MPV) and red cell distribution width (RDW) have been reported as inflammatory markers in patients with inflammatory bowel disease, but they have not been studied in functional gastrointestinal disorders. Aim : To investigate whether there was an association between haemogram parameters (RDW and MPV) and IBS. Material and methods : Forty patients with IBS and 44 healthy controls were included to this retrospective study. Patients diagnosed with IBS according to Rome III criteria were included as the IBS group. They were all screened for psychiatric or organic bowel diseases for the sake of precise diagnosis. Results : Both RDW (p < 0.001) and MPV (p = 0.046) were increased in patients with IBS compared to controls. This increase in RDW and MPV was independent of the type of IBS. Conclusions: The RDW and MPV should be laboratory indicators of IBS. More prospective studies with larger cohorts are needed to confirm our results.